2016
DOI: 10.1007/s11356-016-7406-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metals on rhinosinusal polyposis in Sardinian population (Italy)

Abstract: Metals have strong toxic effects in humans and can act as immunoregulatory factors. The purpose of our study was to determine whether the concentrations of metals are associated with the clinical course of nasal polyposis (NP). We measured the concentrations of 10 metals and non-metal (Zn, Mn, Se, Fe, Cr, Ni, Pb, Al, Cd, and Cu) in 58 patients with NP, and 29 controls with a healthy nasal mucosa. We used electron microscopy to compare the ultrastructural features of the nasal mucosa between NP patients and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Currently, they are being tested several mutated c-Kit inhibitors in the treatment of metastatic disease (imatinib, dasatinib, sunitinib or sorafenib) [ 107 112 ]. Hodi FS et al reported good response on treatment in a patient with KIT mutated rectal melanoma [ 113 ] and Minor DR et al reported a complete remission for 15 months in patients with KIT-mutated underwent to sunitinib treatment [ 114 ]. In a study a patient with mucosal melanoma that received the mTOR inhibitor everolimus constituted a partial response [ 115 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, they are being tested several mutated c-Kit inhibitors in the treatment of metastatic disease (imatinib, dasatinib, sunitinib or sorafenib) [ 107 112 ]. Hodi FS et al reported good response on treatment in a patient with KIT mutated rectal melanoma [ 113 ] and Minor DR et al reported a complete remission for 15 months in patients with KIT-mutated underwent to sunitinib treatment [ 114 ]. In a study a patient with mucosal melanoma that received the mTOR inhibitor everolimus constituted a partial response [ 115 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, IFN-α has been shown to increase degradation of 5-hidroxytryptamine (5-HT) and tryptophan. IFN-α also decreases mRNA levels and protein expression of 5-HT receptor 1A, resulting in down-regulation and thus lower concentration of 5HT [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%